MIS Single-position Lateral and Oblique Lateral Lumbar Interbody Fusion and Bilateral Pedicle Screw Fixation: Feasibility and Perioperative Results. Issue 6 (15th March 2018) - Blizzard, Daniel J.; Thomas, J. Alex
Abstract : Study Design: Retrospective review of prospectively collected data of the first 72 consecutive patients treated with single-position one- or two-level lateral (LLIF) or oblique lateral interbody fusion (OLLIF) with bilateral percutaneous pedicle screw and rod fixation by a single spine surgeon. Objective: To evaluate the clinical feasibility, accuracy, and efficiency of a single-position technique for LLIF and OLLIF with bilateral pedicle screw and rod fixation. Summary of Background Data: Minimally-invasive lateral interbody approaches are performed in the lateral decubitus position. Subsequent repositioning prone for bilateral pedicle screw and rod fixation requires significant time and resources and does not facilitate increased lumbar lordosis. Methods: The first 72 consecutive patients (300 screws) treated with single-position LLIF or OLLIF and bilateral pedicle screws by a single surgeon between December 2013 and August 2016 were included in the study. Screw accuracy and fusion were graded using computed tomography and several timing parameters were recorded including retractor, fluoroscopy, and screw placement time. Complications including reoperation, infection, and postoperative radicular pain and weakness were recorded. Results: Average screw placement time was 5.9 min/screw (standard deviation, SD: 1.5 min; range: 3–9.5 min). Average total operative time (interbody cage and pedicle screw placement) was 87.9 minutes (SD: 25.1 min; range: 49–195 min). Average fluoroscopy time was 15.0 s/screw (SD: 4.7 s; range: 6–25 s). The pedicle screw breach rate was 5.1% with 10/13 breaches measured as < 2 mm in magnitude. Fusion rate at 6-months postoperative was 87.5%. Two (2.8%) patients underwent reoperation for malpositioned pedicle screws with subsequent resolution of symptoms. Conclusion: The single-position, all-lateral technique was found to be feasible with accuracy, fluoroscopy usage, and complication rates comparable with the published literature. This technique eliminates the time and staffing associated with intraoperative repositioning and may lead to significant improvements in operative efficiency and cost savings. Level of Evidence: 4